Developing the performance of female educational supervisors in Jazan region in the view of contemporary trends of educational supervision - Safhi, Aishah Mahah (Journal of Educational and Psychological Sciences, 2023)
The study aimed at identifying the theoretical concepts related to the contemporary trends of educational supervision (supervision by objectives, electronic supervision), showing the reality of the performance of female educational supervisors in Jazan region, finding the application degree of female educational supervisors according to the contemporary trends of educational supervision (supervision by objectives, electronic supervision) during practicing their technical and managerial tasks. Also, The study aimed at identifying the differences of statistical significance among the averages of the study sample responses around the application of female educational supervisors to the contemporary trends of educational supervision according to the variables (scientific qualification - job- years of experience) and providing procedural proposals for the development of female supervisors performance of Jazan region during the application of contemporary trends of educational supervision. The study adopted the descriptive approach. The questionnaire was applied to a random sample of (640) female leaders and teachers at Jazan Administrative educational region, where the number of female leaders was (183) and the number of female teachers was (457). The study indicated the following results: Performance of female educational supervisors in Jazan region is at the (sometimes) level with weighted mean (2,14) since real performance of the female educational supervisors in Jazan region in light of supervision by objectives comes at (mostly) level with weighted mean (2,36), while real performance of female educational supervisors in Jazan region in light of electronic supervision comes at (sometimes) level with a weighted mean (1,92).